SAT0435 MANAGEMENT OF ADVANCED GOUT: A CLAIMS-BASED ANALYSIS FROM THE UNITED STATES. (June 2019) - Lawrence Edwards, N.; Schlesinger, Naomi; Clark, Sanders; Arndt, Theresa; Lipsky, Peter
Abstract : Background: Gout is one of the most common inflammatory arthropathies. Despite available urate lowering therapies (ULT), many patients progress to chronic or advanced gout, characterized by the development of tophi, chronic inflammatory arthritis, and other manifestations resulting from persistent urate deposition. While numerous guidelines exist for the management of gout, there is little information on the frequency of their implementation, especially in patients with advanced gout. Objectives: To evaluate the real-world practice patterns in patients diagnosed with advanced gout using a large administrative claims database from the United States. Methods: We carried out a retrospective analysis of the Symphony Integrated Dataverse to identify patients with advanced gout over an approximately 6-year period from October 2012 to August 2018. Patients were identified as having advanced gout if they were >18 years of age and had at least two medical claims for the diagnosis of gout on different days, separated by at least 3 months. Patients with advanced gout were identified and stratified based on their diagnosis as either chronic gout (ICD-9 274.02, 274.03, ICD-10 M1A.x) or tophaceous gout (ICD-9 274.03, 274.81, 274.82, ICD-10 M1A.xxx1). A third category designated "uncontrolled gout" was clinically defined as any patient with at least three primary diagnoses of idiopathic gout (ICD-10 M10.0x, M1A.0x) along with at least three urate tests (CPT 84550, 84560). Percent and frequency of urate testing, rheumatology specialist visits, and administration of ULT (allopurinol, febuxostat, probenecid, and lesinurad) were evaluated for each diagnostic group. Results: We identified 191, 097 advanced gout patients, including 177, 610 (93%) with chronic gout, 31, 475 (16.5%) with tophaceous gout, and 20, 943 (11%) with uncontrolled gout. 35, 992(18.8%) were coded in more than 1 diagnostic category. The median age was 67 (range: 19-80), 24.7% were female and 75.3% male, with an average of 5.4 years of claims history in the database. As shown in Tables 1 and 2, despite the diagnosis of advanced gout, urate testing, rheumatology consults, and ULT were inconsistent. Urate testing was definitional for uncontrolled gout patients, but was done in less than 65% of patients with the diagnosis of chronic or tophaceous gout and then less than once per year. Similarly, less than 60% of subjects with advanced gout received care by a rheumatologist and less than 80% received ULT and for less than 50% of the year. Conclusion: The subset of patients with advanced gout, identified either as chronic, tophaceous or uncontrolled, received suboptimal care compared to current guidelines. As this group of advanced gout patients is the most affected by urate deposition, added attention should be paid to optimizing their care. Disclosure of Interests: N. Lawrence Edwards Consultant for: Horizon Pharma, Astra Zeneca, Selecta Biosciences, Naomi Schlesinger Consultant for: Astra Zeneca, Novartis, Horizon Pharma, Sanders Clark : None declared, Theresa Arndt: None declared, Peter Lipsky Consultant for: Consulting fees from Horizon Pharma